Karakteristik Masyarakat Tentang Pemberantasan Sarang Nyamuk Demam Berdarah Dengue Dan Keberadaan Jentik - Raimunda Woga; Marieta Kristina Selvi Bai; Syaputra Artama (Alauddin Scientific Journal of Nursing, 2023)
Indonesia as a tropical country and subtropical ranges against dengue. Various efforts are made in the prevention and eradication of DHF, namely by breaking the chain of dengue transmission by preventing vector breeding through Dengue Hemorrhagic Fever Mosquito Nest Eradication (PSN DHF). The hope of the community can be healthier and can minimize the incidence or morbidity or death caused by DHF. The purpose of this study is to identify and analyze community characteristics regarding the eradication of dengue hemorrhagic fever mosquito nests and the presence of larvae. The research method used quantitative research with a descriptive cross-sectional study research design. The population in the study was all residents who were in the Working Area of the Ende City Health Center. The sampling method is carried out by random probability sampling with a target sample number of 85 respondents. Data analysis using chi-square test and pearson chi-squar test. The results found a significant relationship between knowledge (p = 0.013), employment status (p = 0.021) on dengue mosquito nest eradication practices and no significant relationship was found between age (p = 0.151), education level (p = 0.073) on dengue mosquito nest eradication practices. Meanwhile, the conclusions related to the practice of eradicating dengue mosquito nests found a correlation with the presence of mosquito larvae in water reservoirs (p = 0.042). It can be concluded that there is an importance of public awareness of dengue prevention efforts and recommendations to remind each other so that it has a positive impact on improving public health at large.